Reform of the Thai Royal Armed Forces: Guidelines for Constructing a System of Military Professionalization and Reducing the Role of the Royal Thai Armed Forces under the Control of the Civil Government - Norkaew, Yutthasart; Chaowalit, Suthep (Journal of Public Administration Chiang Rai Rajabhat University, 2021)
This academic article aims to study guidelines for constructing a complete system of professionalizing the military [or military professionalism] under the control of the civilian government in Thailand. The article was conducted by investigating academic books, academic research papers, academic articles, and news made available via various media and complying those documented information with the concept on the construction of military professionalism. The data collection was then analyzed to reveal its results and draw further conclusions. The results of this study revealed that the construction of military professionalism under the willingness [or propensity] of civilians to serve in the military is an essential part of the reduction of the military's role under the control of the civilian government. Not only there should be a total separation of the civilians’principle missions from the military ones, but also there should be a mechanism effectively established for the civilian control of the military in accordance with the provisions of the Constitution relating to a functional chain of command between the civilian government and the military. These will devise a method [or a system] of preventing political interference from all stakeholders involved in [a majority of] military coups that had occurred in the past period. That’s to say, the guidelines for constructing a complete system of the construction of military professionalism leading to a reduction in the role of the Thai armed forces under the control of the civil government need to place reliance on 4 supporting factors that can be summarized as follows: The first approach is to amend the Constitution and the Act in respect of military conscription. The amendment should be made under Section 50and Sub-Section 5 prescribed as a person who is forced to serve in the armed forces without their voluntary enlistment. Such a clause can be accounted for a deprivation of the basic human rights of Thai citizens embedded in the constitutional provisions. Thus, any constitutional provisions stipulated in the military conscription should be abolished, leading to constructing a complete system of the military professionalism in Thailand as well. The second approach is to establish a power base for counterbalancing the armed forces by virtue of mobilizing security personnel from the areas of centralized control to the regional areas [of decentralized execution]. It is considered a determinant of future military-led coups and a spectrum of the troops or military staff in competition with a state of preparedness under military chains of command. It also facilitates constructing a complete system of military professionalism without the conscription. The third approach is to create a political culture of civilian sector over military influence. Both the political and military parties should make a collaborate effort to formulate rules on any new administrative values that shall be explicitly stipulated in the Constitution.This will enable to take strict control of the armed forces in accordance with the military chains of command by virtue of promoting awareness of a political culture of civilian sector over military influence. With this respect, all parties should behave with integrity in the reform of the Thai Armed Forces. The fourth approach is to reduce the political role of high ranking officers and retired Army generals. The contributory factor of staging the coup in Thailand was mostly driven in support of a group of retired Army generals who used to hold a senior position in Royal military cadet academy. Thus far, they still exercise their political influence from holding higher positions in state-owned enterprises. In addition, the retired people have the roles to play in parliament as senators appointed by the National Council for Peace and Order (NCPO) after the general election in 2019. It is more difficult to construct a complete professional military system and control the army under a civilian government. Since a group of these people has infiltrated into every government organization or agency and continues to support the existence of a large military organization. It is therefore expedient to reduce the political role of a senior military officer by enacting a law rectified in the prohibition of not being a person holding any position in whether private or public agencies as well as organizations.